Development of fowl cholera vaccine: I. Protection of Pasteurella multocida local isolate vaccine against challenge of homologous and heterologous strains. - Supar .; Yudi Setiadi; Djaenuri .; Nina Kurniasih; Bhakti Poerwadhikarta; Sjafei . (Jurnal Ilmu Ternak dan Veteriner, 2001)
Pasteurella multocida locally isolated from chicken and ducks (BCC 299, BCC 2331, DY1, DY2, 12TG, 15TG) andimported strains (BCC 1359, 1362; HEDDLESTON group 1 and 6 respectively) had been tested for its pathogenicity in theprevious study. The aims of this experiment were to study the preparation of local isolate pasteurellosis vaccines and to determine the protective effect of that vaccines in chicken against the highly pathogenic local isolates of P. multocida. Killed monovalent, bivalent and polyvalent pasteurellosis vaccines were prepared and each was adjunvanted with aluminum hydroxide gel at a final concentration of 1.5% and the cell concentration was equal to the No 10 of MacFarland tube standard. Each of the vaccine prepared was used to vaccinated on a group of six week old of layer chicken (8 per group). Each chicken was subcutaneously injected with 0.2 ml of vaccine, four weeks later each was boostered with similar vaccine with the same dose. Two weeks after giving the boostered vaccine each group of chicken were challenged, half with life bacterium of P. Multocida BCC 2331 and other with DY2. Any chick which survive after challenge was designated as protected by vaccination. Before vaccination 1 ml of blood was drawn from each of chicken and then two weeks apart up to challenge. Serum from each sample was separated and kept in deep freeze until tested by enzyme-linked immunosorbent assay (ELISA). Chicken vaccinated with killed whole cell P. multocida vaccines of monovalent (BCC 2331 or DY2) and bivalent (BCC 2331 + DY2) were protected against challenge with live bacterium of either BCC 2331 or DY2 at rate 67-100%. There was no protection in chicken vaccinated with either BCC 299, DY1, 12TG, 15TG, BCC 1359, or 1362 killed vaccine. Similarly no protection of chicken vaccinated with either DY1 + BCC299, 12TG + 15TG or BCC 1359 + BCC 1362 bivalent vaccines. The protection rate of the polyvalent local isolate vaccine was at average 50-75%. All vaccinated chicken showed the presence of antibody responses againsted the extract cell and whole cell antigens of either P. multocida BCC 2331 or DY2 local isolate as detected by ELISA. The antibody responses from vaccinated chicken against extra cellular antigens prepared from broth cultures of BCC 2331 and DY2 were detected only from vaccinated chicken with vaccine containing killed antigen of BCC 2331 and/or DY2 isolate. It is likely, the local isolate of P. multocida BCC 2331 and DY2 would be benefit for producing inactive fowl cholera vaccine use in Indonesia, but the protective antigen that enhances immune protection should be determined by means of immunoblotting techniques.   Key words: Pasteurella multocida, fowl cholera, vaccine, protection